Bug out! : the world's creepiest, crawliest critters - Clarke, Ginjer L.; Mueller, Pete (New York : Grosset & Dunlap, 2007)
Text and pictures present many strange facts about bugs.
004-up.
Accelerated Reader AR
Keywords: Insects -- Miscellanea -- Juvenile literature; Insects -- Miscellanea